Implementation of Law Enforcement for Business Crime Which is Performed by Illegal Foreign Work - Endeh Suhartini; Rahayu Nuraeni; Edy Santoso; Ani Yumarni (PDIH Untag Semarang, 2023)
The main purposes of this study are: 1) To find out and analyze the forms of business crimes committed by illegal Foreign Workers related to violations of Immigration laws. 2) To find out and analyze immigration law enforcement against illegal Foreign Workers who commit immigration violations. The research method used in this study is a normative juridical study that takes a qualitative approach that looks at and analyzes the legal norms in existing legislation and sociological research as supplementary data to the primary data.The results of this study are: 1) Business crimes committed by illegal foreign workers related to immigration violations, namely the implementation of the Asean Economic Community (AEC) and the introduction of a visa-free policy to encourage and enhance economic growth have an impact on the uncontrolled presence of illegal foreign workers in Indonesia where from the implementation of the AEC and the implementation of the visa-free policy many of the foreign citizens, especially from China who abuse the visa-free policy that should be used for travel but instead used to find work/conduct business activities in Indonesia. 2) Immigration law enforcement against illegal Foreign Workers who commit violations of immigration criminal acts can be prosecuted in two ways, namely the prosecution process in a court or pro justitia and administrative or immigration acts